Mush Amalgamation, Short Residence, and Sparse Detectability of Eruptible Magma Before Andean Super‐Eruptions. (22nd March 2023) - Weber, G.; Blundy, J.; Bevan, D.
Abstract: Giant volcanic eruptions have the potential to overturn civilizations. Yet, the driving mechanism and timescale over which batholithic magma reservoirs transition from non‐eruptible crystal mush to mobile melt‐dominated stages and our capacity to detect a pending super‐eruption remain obscure. Here we show, using Sr isotope zonation in plagioclase crystals from three Andean large‐magnitude eruptions (Atana, Toconao, and Tara ignimbrites), that eruptible magma forms by amalgamation of isotopically diverse crystal populations and silicic melt without large‐scale reheating. In each case, crystals record large isotopic diversity in crystal cores, converging toward a common value in crystal rims that coincides with the composition of the rhyolitic carrier melt. Using diffusion chronometry, we show that the assembled magma resided pre‐eruptively in the crust for timescales of no more than decades to centuries for Atana and Tara, but up to several millennia for Toconao. These timescales and isotopic observations are consistent with the accumulation and destabilization of melt‐rich layers in crystal mush. While the prospect of capturing such melt lenses with most geophysical monitoring techniques is pessimistic, gravity modeling indicates that such structures are potentially resolvable. Our findings provoke a new assessment of the origin and hazards associated with large magnitude explosive eruptions. Plain Language Summary: Super‐eruptions are the largest manifestation of explosive volcanism on Earth. If such an event would occur today, it could deeply impact human civilization on a global scale. Yet, signals that may emerge prior to such eruptions are difficult to constrain. To gain greater understanding of the mechanisms and timescales over which giant, eruptible, reservoirs form, and to evaluate our capacity of capturing the evolution toward large eruptions, we studied plagioclase crystals, a mineral that is an excellent recorder of magmatic processes. For three large eruptions in the Central Andes, we analyzed strontium isotopes in traverses from crystal cores to rims to provide a temporal record of melt composition. Our results show that, in each case, the eruptible magma amalgamated from distinct pre‐existing magma pockets that merged prior to eruption. This merged state of the magma did not exist for longer than a few hundred to thousands of years based on the preservation of the crystal strontium‐isotope traverses at high temperatures. These results are consistent with the destabilization of melt‐rich layers on timescales comparable to human lifespans. Although most geophysical imaging methods are unlikely to capture this process, our calculations indicate that gravity monitoring of super‐volcanoes can potentially resolve such structures. Key Points: Sr‐isotopes in plagioclase record the emergence of eruptible magma through amalgamation of pre‐existing mush in the Central Andes The amalgamated magma did not reside at depth for longer than centuries to millennia based on diffusion chronometry Forward modeling indicates that high‐precision gravity monitoring has large potential to resolve eruptible magma amalgamation